2004
DOI: 10.1002/joc.1102
|View full text |Cite
|
Sign up to set email alerts
|

Trends in precipitation on the wettest days of the year across the contiguous USA

Abstract: Over the course of the 20th century, average annual precipitation for the contiguous USA has increased by nearly 10%. This increase has been described as being dominated by 'disproportionate' increases in extreme precipitation events. However, methodological constraints have confounded detailed interpretation of such results. Here, we briefly describe those limitations and re-evaluate the nature of the observed precipitation changes using a method that allows for a more accurate examination of changes in the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 7 publications
4
31
0
1
Order By: Relevance
“…The changing contribution of the "30-year 10th decile" rainfall events to total annual rainfall can thus be determined. This method extends previous analyses of heavy rainfall using a "frequency-quantile" approach (Karl & Knight, 1998), which has been challenged for failing to distinguish between "disproportional" changes in extreme events, compared to the mean of the skewed distribution of daily rainfall totals (Michaels et al, 2004).…”
Section: Methodology Upper Percentiles Of Daily Precipitationmentioning
confidence: 97%
“…The changing contribution of the "30-year 10th decile" rainfall events to total annual rainfall can thus be determined. This method extends previous analyses of heavy rainfall using a "frequency-quantile" approach (Karl & Knight, 1998), which has been challenged for failing to distinguish between "disproportional" changes in extreme events, compared to the mean of the skewed distribution of daily rainfall totals (Michaels et al, 2004).…”
Section: Methodology Upper Percentiles Of Daily Precipitationmentioning
confidence: 97%
“…Multi-decadal variability in annual rainfall totals can cause the strength and/or even the sign of an extrapolated trend to change depending on the period and/or length of record chosen (Figure 3). Others have demonstrated that misleading trends can be an artefact of the statistical method used to divide data, such as percentile-based indices for temperature 1960 1965 1970 1975 1980 1985 1990 1995 2000 2005 Total (mm) and precipitation extremes (Michaels et al, 2004;Zhang et al, 2005).…”
Section: Trend Extrapolationmentioning
confidence: 99%
“…However, in recent decades an increasing number of researchers have been involved in gathering available meteorological records for specific regions (digitizing them when necessary and assessing their quality and homogeneity) in order to devise indices comparable to those recommended by the WMO CC1/COVER/JCOMM Expert Team on Climate Change Detection and Indices (http://cccma.seos.uvic.ca/etccdi). As a result it has been possible to undertake trend analyses on daily precipitation indices in widely separated and contrasting geographical areas including the US (United States) (Michaels et al, 2004), Central and South America (Aguilar et al, 2005), the UK (Osborn et al, 2000), Central and Western Europe (Moberg and Jones, 2005), Germany (Zolina et al, 2008), Switzerland (Schimidi and Frei, 2005), some parts of the Iberian Peninsula (Lana et al, 2004, Martín-Vide, 2004;Casas et al, 2007;Martínez et al, 2007;Rodrigo and Trigo, 2007), Italy (Brunetti et al, 2000(Brunetti et al, , 2001, the Mediterranean region (Norrant and Douguédroit, 2006), India (Sen-Roy and Balling, 2004), Mongolia (Nandinsetseg et al, 2007), Australia (Suppiah and Hennessy, 1998;Haylock and Nicholls, 2000), New Zealand (Salinger and Griffiths, 2001), South Africa (Kruger, 2006), and South East Asia and the South Pacific (Manton et al, 2001;Griffiths et al, 2003).…”
Section: Introductionmentioning
confidence: 99%